How Can Preservice Teaching Programs Help New Teachers Feel Prepared to Address Absenteeism?. Issue 5 (May 2020) - Gottfried, Michael A.; Kirksey, J. Jacob; Hutt, Ethan
Background: Though policy makers are beginning to hold schools accountable for reducing chronic absenteeism, little attention has been paid to the role of teachers. No known study has examined whether rising cohorts of new teachers feel prepared to address this challenge. This is particularly problematic given that teachers with less experience tend to be less efficacious at reducing students' absences. Research Questions: (1) Do newly graduating teachers feel as if they have sufficient knowledge about chronic absenteeism? (2) Do newly graduating teachers feel prepared to address absenteeism? (3) Do these perceptions differ by elementary versus secondary preservice graduates? Subjects: Our study collected survey data from the 2017–2018 graduating cohort of general education teacher candidates from a statewide university system in California. This system prepares, on average, 800 teaching candidates a year, and all general education candidates participate in teacher licensure. We surveyed the teaching candidates in the 2017–2018 graduating cohort from these campuses and had a response rate of 60%. Survey measures included teacher background data and perceptions of the effectiveness of their preparation programs, knowledge of absenteeism, and perceived ability to address absenteeism. Research Design: We began with a baseline model in which our outcome measures (knowledge and ability to address absenteeism) were regressed on teachers' background characteristics and perceptions of the efficacy of their preparation programs. We augmented this model by including university fixed effects, such that we only explore variation within program rather than across universities. Results: Our findings suggest that preservice teachers who found their programs to be helpful, who felt supported by supervisors, and who found usefulness in their field placements also felt as though they had greater knowledge about chronic absenteeism and how to address it. The results were differentiated by elementary versus secondary candidates. Conclusions: Given our students' extreme rate of missing school days, it is of immediate importance to determine if we are preparing our nation's newest teachers to help address the current crisis. Our study fills this gap by looking at the influence that teacher education programs (specifically teacher licensure requirements) might have in contributing to teachers' perceptions of being prepared to graduate and attend to attendance.